Liberação controlada de nutrientes e novos sistemas para avaliação de espécies químicas empregadas na fertilização - Antonietti, Thales Gonzaga [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper focused on fertilization procedures (nitrogen, potassium and phosphorous) in Agriculture. We have undertaken an investigation of new materials for coating surfaces of fertilizer and also studied methodologies of measurement, aiming to evaluate the performance of the products in measures of CRF (Controlled Release of Fertilizer), with direct applications in products and processes. The polymer used to coat urea, KCl and MAP (monoammonium phosphate) was developed based on a styrenated acrylic resin. In the formulation of the polymer application were used as sugar cane molasses and vinasse compounds and on the application process was added CaCO3 or CaSO4, with these decisive role in gradual release process by a cation exchange mechanism that promotes preferential release of ammonium. This paper presents a summary on the topic, reactions, structures and chemical properties related to the dissolution controlled urea and other nutrients survey. The polymer used to control the process of the slow release of the species soluble in water (moisture) of the soil was assessed from measurement techniques based on accelerated dissolution in aqueous systems, developed employing Condutometry and Potentiometry (Ion Selective Electrode). Also was investigated comparatively the salt effect of KCl and KCl coated on the ground. The polymer was chemically designed to display favorable structural and chemical properties focusing on nutrient economy (reduction of applied doses). The modified polymer applied in the lining of the nutrient was characterized by thermal analysis of DSC (Defferential Scanning Calorimetry) and TG (Thermogravimetry), in order to determine the properties and characteristics of the polymer, such as glass transition and stability. It was found through these analysis that the modification made in the polymer changes some of its physical and chemical characteristics, as the reduction in glass...

Este trabalho focalizou procedimentos de fertilização (nitrogenada, potássica e fosfórica) na Agricultura. Investigou-se novos materiais para revestir superfícies de fertilizantes e, também, estudou-se metodologias de medidas visando avaliações de desempenho dos produtos em medidas de CRF (Controlled Release of Fertilizer), com aplicações diretas em produtos e processos. O polímero utilizado no revestimento de uréia, KCl e MAP (monoamônio fosfato) foi desenvolvido à base de uma resina acrílica estirenada. Na formulação do polímero de aplicação foram utilizados compósitos como melaço-de-cana e vinhaça e no processo de aplicação foi adicionado CaCO3 ou CaSO4, estes com papel determinante no processo de liberação gradual, através de um mecanismo de troca catiônica que promove a liberação preferencial de amônio. Neste trabalho apresenta-se um levantamento resumido sobre o tema, reações, estruturas e propriedades químicas relacionadas com a dissolução controlada de uréia e dos outros nutrientes. O polímero usado para o controle do processo de liberação lenta das espécies solúveis na água (umidade) do solo foi avaliado a partir de técnicas de medidas baseadas em sistemas de dissolução acelerada em meio aquoso, desenvolvidas empregando-se Condutometria e Potenciometria (Eletrodo de Íon Seletivo). Também foi investigado comparativamente o efeito salino do KCl e KCl revestido no solo. O polímero foi desenhado quimicamente para exibir propriedades estruturais e químicas favoráveis com foco na economia de nutrientes (redução de doses aplicadas). O polímero modificado empregado no revestimento dos nutrientes foi caracterizado através das análises térmicas DSC (Defferential Scanning Calorimetry) e TG (Thermogravimetry), visando a determinação de propriedades e características específicas do polímero, como a transição vítrea e a estabilidade. Verificou-se...
Keywords: Ureia como fertilizante; Amonio; Tecnologia de liberação controlada; Agricultura organica; Agricultura sustentável; Organic agriculture